Ocena moralna czynów przestępczych, pozytywnych oraz budzących społeczne kontrowersje w percepcji młodzieży = Moral evaluation of criminal, positive, and socially controversial acts as perceived by youth - Doliński, Artur (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents results of research on how youth perceives various social acts. The perception was mirrored in moral evaluation of behavior (describing the level of condemnation and the harmfulness of the act) as well as the level of rigorism. The analyzed behavior was divided into that related to morals, religion, politics, nationality issues, and anti-social attitudes.
Keywords: młodzież szkolna; moralność